2001
DOI: 10.1080/13562510120078018
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning Generic Skills in Universities: The case of 'sociology' in a teacher education programme

Abstract: The paper examines the links between a recent focus in Australian universities on 'generic skills' or 'graduate qualities', and national employment policies directed at developing employment-related 'key competencies'. It examines the attempt by a team of teacher educators in Australia to develop curricula that would meet the goals of national workplace policy initiatives, while retaining the traditional university concern of teaching critical evaluation of information and social practice. The speci c example … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…However, the findings suggest that teaching style did not influence adopted learning approaches. It would seem that other factors, such as course structure, delivery and assessment activities may not communicate the need for (and reward) the use of deeper, self-regulated and cognitive organisation strategies (Patterson & Bell, 2001). This is in support of previous research suggesting that students will adopt surface learning approaches if that is seen to be what is (visibly) rewarded (Deeter-Schmelz, Kennedy, & Ramsay, 2002;Ramsden, 1992).…”
Section: Conclusion and Future Directions (Cycle 3)supporting
confidence: 76%
“…However, the findings suggest that teaching style did not influence adopted learning approaches. It would seem that other factors, such as course structure, delivery and assessment activities may not communicate the need for (and reward) the use of deeper, self-regulated and cognitive organisation strategies (Patterson & Bell, 2001). This is in support of previous research suggesting that students will adopt surface learning approaches if that is seen to be what is (visibly) rewarded (Deeter-Schmelz, Kennedy, & Ramsay, 2002;Ramsden, 1992).…”
Section: Conclusion and Future Directions (Cycle 3)supporting
confidence: 76%
“…They found that commitment from staff, signi®cant investment in staff development, and procedures for monitoring the effectiveness of the framework were considered vital for the success of this project. Van Schalkwyk (2002) and Patterson and Bell (2001) reiterated these points and also highlighted the need for assessment to re¯ect the resulting changes in course content. Alverno College in the USA is an exemplar in this area.…”
Section: Introductionmentioning
confidence: 94%
“…Consideration of non-content-related skills is not new, with papers on the topic dating from the 1950s (Leveson, 2000). However, in Australia, the level of attention focused on skills has increased signi®cantly over the last 10 years (Clanchy & Ballard, 1995;Lake & Kemp, 1996;Dorfman & Taylor, 1998;Patterson & Bell, 2001). Given this long history, it is interesting that we are still talking about the importance of these skills, graduates' lack of them and how best to teach and promote them.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation